2018
DOI: 10.1002/smll.201703510
|View full text |Cite
|
Sign up to set email alerts
|

Reactivating Catalytic Surface: Insights into the Role of Hot Holes in Plasmonic Catalysis

Abstract: Surface plasmon resonance of coinage metal nanoparticles is extensively exploited to promote catalytic reactions via harvesting solar energy. Previous efforts on elucidating the mechanisms of enhanced catalysis are devoted to hot electron-induced photothermal conversion and direct charge transfer to the adsorbed reactants. However, little attention is paid to roles of hot holes that are generated concomitantly with hot electrons. In this work, 13 nm spherical Au nanoparticles with small absorption cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…The roles of holes in photocatalytic processes are typically complicated. 47 because SiC is an n-type semiconductor. In this process, SiC provides low-energy electrons to Au and receives hot electrons from Au.…”
Section: Resultsmentioning
confidence: 99%
“…The roles of holes in photocatalytic processes are typically complicated. 47 because SiC is an n-type semiconductor. In this process, SiC provides low-energy electrons to Au and receives hot electrons from Au.…”
Section: Resultsmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) excited the illuminated AuNPs to decay into energetic hot electrons. Hot electron transfer (HET) can promote many chemical reactions [ 59 , 60 , 61 ], including the dissociation of hydrogen [ 62 ], activation of oxygen [ 63 ], and electrocatalytic hydrogen evolution [ 64 ]. On the other hand, our group proposed an innovative method to create plasmon-activated water (PAW), which is prepared by treating deionized (DI) water with resonantly excited AuNPs [ 23 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Hot charge carriers, including hot electrons and hot holes, generated by plasmonic illuminations play synergistic roles in enhancing catalytic performance. [5][6][7] However, determining activation energies and rate limiting step under illumination condition and exploring the contribution of hot carrier reduced activation barrier is still rare and controversy. 1,8 For example, El-Sayed and coworkers found that the activation barrier for hexacyanoferrate (III) reduction on Au NPs was slightly higher under visible light excitation than that in the dark, even though the reaction rate was accelerated under light.…”
mentioning
confidence: 99%